2002
DOI: 10.1093/jn/132.11.3394
|View full text |Cite
|
Sign up to set email alerts
|

Melibiose, Difructose Anhydride III and Difructose Anhydride IV Enhance Net Calcium Absorption in Rat Small and Large Intestinal Epithelium by Increasing the Passage of Tight Junctions In Vitro

Abstract: An Ussing chamber technique was used to determine the effects of three indigestible disaccharides on net Ca transport from the luminal side to the basolateral side of isolated preparations of jejunal, ileal, cecal and colonic epithelium in rats. Permeability of Lucifer Yellow (LY) and transepithelial electrical resistance (TEER), which are indicators of intercellular passage of the intestinal mucosa, were also determined. The concentrations of Ca in the serosal and mucosal media were 1.25 mmol/L and 10 mmol/L,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 27 publications
1
73
0
2
Order By: Relevance
“…Dose-dependent enhancement by DFAIII of calcium excretion has also been demonstrated by the Ussing chamber technique. 4) It is therefore intriguing that the results obtained from different types of experiment are very similar in respect of dose-dependent enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dose-dependent enhancement by DFAIII of calcium excretion has also been demonstrated by the Ussing chamber technique. 4) It is therefore intriguing that the results obtained from different types of experiment are very similar in respect of dose-dependent enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated by the Ussing chamber technique with rats that the calcium absorption in all gastrointestinal areas was dose-dependently stimulated by DFAIII. 4) It has been also clarified that the mechanism for such stimulation involved active transport through the tight junction of the enteric canal. 4) However, it is unclear whether the stimulation of calcium absorption in the present study was caused by the same mechanism or not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The growing broilers need to deposit higher levels of protein and minerals in the carcass to ensure maximum muscle and bone growth. The use of oligosaccharides improves the intestinal absorption of minerals in rats and humans (Ohta et al, 1998;Mineo et al, 2002); however, this effect has been poorly studied in birds (Oliveira et al, 2009). In this study, a greater body retention of minerals was not observed, possibly because whole yeast cell was used instead of isolated MOS, and lower concentrations of MOS are found in the whole yeast cell.…”
Section: Resultsmentioning
confidence: 53%